Epoxyeicosanoids in hypertension - Imig, J D (Physiological research, 2019)
Epoxyeicosatrienoic acids (EETs) are also known as epoxyeicosanoids that have renal and cardiovascular actions. These renal and cardiovascular actions can be regulated by soluble epoxide hydrolase (sEH) that degrades and inactivates EETs. Extensive animal hypertension studies have determined that vascular, epithelial transport, and anti-inflammatory actions of EETs lower blood pressure and decrease renal and cardiovascular disease progression. Human studies have also supported the notion that increasing EET levels in hypertension could be beneficial. Pharmacological and genetic approaches to increase epoxyeicosanoids in several animal models and humans have found improved endothelial vascular function, increased sodium excretion, and decreased inflammation to oppose hypertension and associated renal and cardiovascular complications. These compelling outcomes support the concept that increasing epoxyeicosanoids via sEH inhibitors or EET analogs could be a valuable hypertension treatment.
Keywords: ikosanoidy; inhibitory enzymů; signální transdukce; Signal Transduction; Animals; Humans; Antihypertensive Agents; krevní tlak; antihypertenziva; lidé; Blood Pressure; hypertenze; zvířata; Eicosanoids; epoxid hydrolasy; Enzyme Inhibitors; Epoxide Hydrolases; Hypertension